La tutela del consumidor sobreendeudado en el derecho argentino - Beltramo, Andrés Nicolás (2014)
Over-indebtedness is a social phenomenon to which law must provide\na solution. The aim of this article is to analyze, on the one hand, whether and how\nArgentinean defences to contract enforceability (e.g. usury), bankruptcy law, and consumer\nlaw apply in case of over-indebtedness and, on the other hand, how Argentinean\nconstitutional rights may be balanced in such case